Firm selection and corporate cash holdings - Begenau, Juliane; Palazzo, Berardino (Journal of Financial Economics, 2021)
Since the early 1980s, the composition of US public firms has progressively shifted toward less profitable firms with high growth potential (Fama and French, 2004). We estimate a dynamic corporate finance model to quantify the role of this selection mechanism for the secular trend in cash holdings among US public firms. We find that an increase in the precautionary savings motive—primarily driven by the decline in initial profitability among R&D-intensive new lists—explains about 50% of the upward trend in cash holdings. This selection mechanism also explains part of the upward trend in sales growth volatility.